Effect of long-acting β2-agonists olodaterol and formoterol on heart rate and blood pressure in chronic obstructive pulmonary disease patients. (October 2018) - Andreas, Stefan; Bothner, Ulrich; Trampisch, Matthias; Haensel, Michaela; Buhl, Roland; Alter, Peter
Abstract: Background: Cardiovascular comorbidities are common in chronic obstructive pulmonary disease (COPD), and elevated heart rate reflects increased cardiovascular risk over time, which is associated with unfavourable neurohumoral activation. Long-acting β2 -agonists (LABAs) are established treatments in COPD, but potentially increase heart rate. We report a post hoc pooled analysis of the effect of olodaterol (5 or 10 μg) or formoterol (12 μg) on heart rate and blood pressure (BP) in Global Initiative for Chronic Obstructive Lung Disease Stage 2–4 COPD patients. Methods: Four randomised, double-blind, placebo-controlled, Phase III studies were analysed. Changes in heart rate and systolic/diastolic BP were measured before and after dosing with the study medication at each visit. Results: At each study visit, the increase in pre-dose heart rate was numerically lower with both LABAs compared with placebo. Systolic and diastolic BP were decreased with all treatments. Short-term (pre-dose to 40 min post-dose) effects of drug administration on heart rate were small and similar for all treatment arms (between −3 and +1 beats per minute). Conclusion: Heart rate and BP were not adversely influenced in this study involving long-term administration of olodaterol or formoterol in patients with moderate-to-severe COPD. This supports the cardiovascular safety of LABAs in COPD maintenance treatment.